Determination Of Ivermectin, Albendazole & Diethyl Carbamazine Citrate By Using LCMS/MS (Journal of Namibian Studies : History Politics Culture, 2023)
An accurate LC-MS/MS method was established and validated to study the pharmacokinetic properties of Ivermectin (IVER) Albendazole (ALB) & Diethylcarbamazine (DEC) in the plasma of rat using carbamazepine (CBZ) as internal standard (IS). For the extraction of a combination of IVER, ALB, and DEC from rat plasma, the protein precipitation method was used. The monitored MS/MS ion transitions were 897.6 → 753.4 for IVER, 200 →127 for DEC, 266.1→234 for ALB, and, 237→ 194 for Carbamazepine. The method's lower limit of quantitation (LLOQ) was 11.41 ng/ml for ALB and DEC and for IVER, it was 46.87ng/ ml in rat plasma with a mean recovery of 81.22%. for ALB, 80.24%. for DEC and 77.66%. for IVER. The fine chromatographic separation and resolution of peaks have been attained with 25 mM Ammonium formate in water and 0.1 % formic acid in methanol on the Kinetex Evo C18 column. The total run time for the method was 7 minutes. The method was found to be accurate and precise with a linearity range of 46.87 ng/mL to 24000 ng/ mL for IVER and 11.71 ng/mL to 6000 ng/ mL for ALB as well as DEC with a correlation coefficient (r) of 0.9977, 0.9990, 0.9994 respectively.